An Investigation on Purchasing Behavior of Piracy Software by Customers in Kuala Lumpur - Xu, Meng Xue (2014)
Software piracy is becoming an increasingly critical problem around the world. Compared to software industry, the speed of development for pirating software is an increasing problem. At the meantime, the software piracy rate in Malaysia is relatively higher as compared to other countries in Asia Pacific such as Singapore and Hong Kong. Studies specifically on Malaysia software piracy problem is very limited. And hence, the problem of software piracy in Malaysia is worth to be studied and worked on. This study focuses on the factors that influence Malaysians’ intention to purchase pirate software and is using the Theory of Planned Behavior (TPB) as a theoretical framework to develop the hypothesis. The TPB model uses three different factors to examine the intention to indulge in software piracy. These factors were attitude, perceived behavioral control and subjective norms. Two additional factors from other researchers were included in the model are past piracy behavior and moral obligation. From these five factors, resulted in five hypothesis used in this study. In order to analyze the factors, quantitative method was used as the methodology to investigate the factors influencing Malaysians’ intention to purchase pirate software. The respondents used in this study are working adults who are above 18 years of age. The sample used in this study is 270. Descriptive analysis is used to analyze the demographic information of the participants, and it is followed by reliability and validity test to analyze the factors. The result of this study indicated that the entire hypotheses in the study are supported. Using these results, a better understanding of why individuals in Malaysia have the intention to purchase pirate software was obtained. Finally recommendations were made to help combat software piracy in Malaysia.